Financial Cycles Nature and its Role in the Crisis Processes Development - Usik, I.A. (Економічний вісник Донбасу, 2015)
The essence of financial cycles and features of their display: a longer period in comparison with the economic cycles, following the phase of the crisis after the cycle peak, more severe recession. Identified key indicators of the financial cycle: credit composes (the ratio of loans to GDP, the growth rate of credit resources, the ratio of credit to the assets of the banking system) and the dynamics of real estate prices. The dynamics of these manifestations in Ukraine indicators and directions to minimize the impact of the financial cycle.